2021
DOI: 10.1212/wnl.0000000000011998
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Dysfunction and Risk of Sudden Unexpected Death in Epilepsy

Abstract: Objective:We aimed to test whether patients who died from sudden unexpected death in epilepsy (SUDEP) had an abnormal cardiac autonomic response to sympathetic stimulation by hyperventilation.Methods:We conducted a retrospective, observational, case-control study of a group of patients who died from SUDEP and controls who were matched with the patients for epilepsy type, drug resistance, sex, age at electroencephalogram recording, age at onset of epilepsy, and duration of epilepsy. We analyzed the heart rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Of these, 24 articles were excluded (see Table S3 for exclusion reasons). Only seven retrospective studies (five case-control studies and two case reports) fulfilled the selection criteria and accessed the following steps (Figure 1) [29,[33][34][35][36][37][38].…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 24 articles were excluded (see Table S3 for exclusion reasons). Only seven retrospective studies (five case-control studies and two case reports) fulfilled the selection criteria and accessed the following steps (Figure 1) [29,[33][34][35][36][37][38].…”
Section: Literature Searchmentioning
confidence: 99%
“…Generally, if multiple EEG + ECG recordings were available, the one with the best ECG data quality was chosen. In all but one study [34], HRV analysis was performed in a resting-state condition (i.e., patients lying on the bed with a normal breathing rate).…”
Section: Ecg Recording and Data Lengthmentioning
confidence: 99%
“…In a recent study, the researchers analyzed HR and HRV of the patients at rest and during and after hyperventilation performed during the last EEG recording before SUDEP. They found that they had aberrant cardiac autonomic responses to sympathetic stimulation due to hyperventilation, thus suggesting that an index based on HR change on hyperventilation could be used to select patients at risk of SUDEP 48 …”
Section: Sudep Pathogenesismentioning
confidence: 99%
“…They found that they had aberrant cardiac autonomic responses to sympathetic stimulation due to hyperventilation, thus suggesting that an index based on HR change on hyperventilation could be used to select patients at risk of SUDEP. 48 Therefore, ictal autonomic changes may serve as clues to diagnosis and provide targets for seizure detection, thus helping us to understand the mechanism of SUDEP. Furthermore, monitoring autonomic changes through wearable devices can be conducive to SUDEP prevention.…”
Section: Sudep Pathog Ene S Ismentioning
confidence: 99%
“…There is a higher susceptibility to autonomic disturbances in refractory epilepsy, in close temporal relation to seizures, and in SUDEP cases. [20][21][22][23][24][25] Interictal sympathetic overactivity is seen in most epilepsy, 26 and decreased vagal function is associated with a higher risk of SUDEP. 27 Autonomic measures have been shown to be lower in people with Dravet syndrome compared to healthy controls.…”
mentioning
confidence: 99%